Reversing the Process of Nationalization: Effects and Hazards of New Legislation in Britain - Hobson, Oscar (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 1953)
SummaryAfter carrying during the previous half-century a nationalization legislation, Great Britain by the recent Royal assent given to the Transport Act and the Iron and Steel Act, has brought on denationalization of these industries concerned. The Author comments briefly on this important question considering the Transport denationalization as a more difficult and hazardous measure than the Iron and Steel denationalization. In concluding, the Author hopes that both Transport and Steel Acts will at least be successful in securing the removal of their subjects from the party arena.